Remoção de metais de águas utilizando biossorventes de castanha de caju, caroço de açaí e castanha do Brasil modificados quimicamente - Coelho, Gustavo Ferreira (2016)
The aim of this study was to evaluate the use of cashew nut shell - CNS - (Anacardium occidentale), endocarp of Euterpe – CA – (Euterpe oleraceae) e Brazil nuts – BN –(Bertholletia excelsa), after chemical modification with H 2 O 2 , H 2 SO 4 and NaOH in the removal of metal ions Cd 2+ , Pb 2+ and Cr 3+ aqueous medium. Therefore, the adsorbent was characterized as the presence of total, elements, structure, infrared spectroscopy (IR), morphological, by scanning electron microscopy (SEM), and point of zero charge (pH PCZ ), mass loss by thermogravimetry (TG) and specific surface area (SSA), size and pore volume (BET). After that, tests were conducted to determine the optimal conditions (pH, mass of adsorbent) adsorption by means of multivariate analysis with Central Composite Rotational Design (CCRD). The adsorption kinetics was evaluated by the pseudo-first, pseudo-second, Elovich and intraparticle diffusion mathematical models, and sorption isotherms were linearized mathematical models according to Langmuir, Freundlich and Dubinin-Radushkevich (D-R). The effect of initial concentration, temperature in the process, desorption were also performed. By SEM it was observed that the CNS, CA and BN had irregular, spongy and heterogeneous structure, and the IR may be the presence of hydroxyl groups, aliphatic, phenolic, carboxylic acid, both analyzes giving the adsorbent characteristics favorable to adsorption. The pH PCZ of the adsorbent demonstranted change by the solutions in all adsorbents. The optimum adsorption conditions of Cd 2+ , Pb 2+ and Cr 3+ were: pH: 5.0; mass of adsorbent: 4 g L -1 and 40 min equilibration time. The models pseudo-second order and D-R suggested the predominance of chemisorption in the process. The highest removal efficiency was obtained in the initial concentrations, with high rates of desorption to Cd 2+ and Pb 2+ and low desorption to Cr 3+ . Most of the materials adjustment of the Langmuir and the others suggested to Freundlich adsorption suggested the occurrence of both, mono or multilayers adsorption, but prevailing the adsorption monolayer. The thermodynamic study showed that the process was spontaneous. CNS, CA and BN has the potential to increase the removal efficiency of Cd Pb and Cr, when chemically modified with H 2 O 2 , H 2 SO 4 and NaOH.